2000
DOI: 10.1523/jneurosci.20-01-00451.2000
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Recognition Memory in Monkeys after Damage Limited to the Hippocampal Region

Abstract: Monkeys with lesions limited to the hippocampal region (the hippocampus proper, the dentate gyrus, and the subiculum) were impaired on two tasks of recognition memory: delayed nonmatching to sample and the visual paired-comparison task. Recognition memory was impaired in five different groups of monkeys, whether the lesions were made by an ischemic procedure, by radio frequency, or by ibotenic acid. The finding that the hippocampal region is essential for normal recognition memory performance is considered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
357
1
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(393 citation statements)
references
References 50 publications
30
357
1
5
Order By: Relevance
“…This theory, then, explains the delay-dependent deficits seen by Zola et al [253] as reflecting a loss of contextual-memory. If we ask how an animal can solve the DNMS task, we see that both active memory and content-addressable-memory mechanisms would be helpful.…”
Section: Slipping Out Of Contextmentioning
confidence: 83%
See 3 more Smart Citations
“…This theory, then, explains the delay-dependent deficits seen by Zola et al [253] as reflecting a loss of contextual-memory. If we ask how an animal can solve the DNMS task, we see that both active memory and content-addressable-memory mechanisms would be helpful.…”
Section: Slipping Out Of Contextmentioning
confidence: 83%
“…By pooling across the groups, a population could be generated with 18 lesioned animals. These animals showed small but significant deficits even in the 15 s condition [253].…”
Section: Slipping Out Of Contextmentioning
confidence: 87%
See 2 more Smart Citations
“…Increasing evidence suggests that the neuronal interaction between hippocampus and neocortex also plays an important role in memory formation (Jutras et al, 2009;Sirota et al, 2003) and memory functions degrade after damage to the hippocampus (Manns et al, 2003;Zola et al, 2000). Interestingly, we found that the left and right temporal lobes turn out to be the driving forces for the highfrequency overconnectivity in older age, which is directly related to cognitive decline.…”
mentioning
confidence: 57%